Identification of Parasitic Worms in Tilapia (Oreochronis niloticus) in Tanjung Bunga Lake, Makassar City - Amalia, Ummu; Adyatma Muhammad Nur; Rian Hari Suharto; Mursalim, Muhammad Fadhlullah (Universitas Airlangga, 2025)
In the cultivation of tilapia (Oreochromis niloticus), parasitic worms can be detrimental in the form of mortality, resulting in increased financial losses. This study aimed to detect and identify parasitic worms in tilapia cultivated in Tanjung Bunga Lake. This study was conducted in March-April 2024. Fifty eight tilapia fish samples were randomly sampled at seven lake points and water sample for water quality examination including pH, salinity, temperature, dissove oxigen, nitrate, nitrite, and amonia. The identification results showed that only Cichlidogyrus sp. were worm parasites found in tilapia samples. This research indicates that Cichlidogyrus is the most frequent worm infecting the gills of tilapia in the lake, which could result in greater financial losses and a decline in health for fish producers in the region. The results emphasize the necessity of efficient management strategies to minimize parasitic infections in tilapia aquaculture systems.